CO-GAS PRODUCTION FROM PYROLYSIS AND GASIFICATION OF AGRICULTURAL BIOWASTE OF SORGHUM ROOT WITH WASTE WOOD AND TURKISH COALS IN RETORT AND BIOGAS - Tosun, Yildirim Ismail (Stef92 Technology Ltd, 2015)
In order to diminish the negative facts of scarce primary energy resources, increasing energy needs and greenhouse gases, alternative clean and renewable energy sources have become important research topics of this century. This project is regarding the main subject of Biomass; as clean, renewable and sustainable alternative energy source. Although we mention a much broader definition of Biomass in this study, the forest and wood waste, forest residue of any kind incurred during harvest, the fine-scale firewood, twigs, bark, cones, etc. are defined as an organic waste mass. Turkey's forest biomass potential is quite high. 27% of the total area of Turkey covers as forest area, an area of 21 million hectares. Forest rehabilitation, maintenance and harvest result in no commercial value waste mass of about 7 million tons per year in forest sector emerging now. Turkish lignite, clean product of pyrolysis with the production of liquid fuels will enable the development of South-East Anatolia and will also further enhance industrial development and diversification and supply of industrial energy fuel.
15th International Multidisciplinary Scientific Geoconference (SGEM) -- JUN 18-24, 2015 -- Albena, BULGARIA
Keywords: biogas; coal and biomass gas; wood gasification